Healthcare worker compliance with cervical cancer screening guidelines. An audit at district and regional level of care in the Pietermaritzburg Metropolitan area of KwaZulu-Natal - Mbali T. Makhubo; Thinagrin D. Naidoo (AOSIS, 2020)
Background: In South Africa (SA) there are screening guidelines for cervical cancer in women living with HIV (WLWH). To our knowledge there is lack of data concerning the knowledge of health care workers (HCWs) about cervical cancer screening guidelines before the initiation of antiretroviral therapy (ART) in WLWH. Objectives: To investigate the knowledge and familiarity of HCWs regarding cervical cancer screening guidelines in WLWH. Methods: A cross-sectional questionnaire-based study exploring compliance with cervical cancer screening guidelines before initiating ART was conducted with 85 HCWs in the antiretroviral (ARV) clinics of a district and regional hospitals in KwaZulu-Natal, SA. Data were analysed using Stata V13 and a p-value of ≤ 0.05 was considered statistically significant. Results: Eighty-five HCWs were included in the study. Health care workers' responses to knowledge about cervical cancer screening in WLWH were suboptimal and revealed significant gaps. Most HCWs did not know the screening intervals of WLWH. Statistically significant associations were found between an HCW's occupation and responses to the Likert scale questions. Conclusion: Although the majority of HCWs were familiar with cervical cancer screening guidelines in WLWH, the study highlights that there are deficiencies in both knowledge and practice. Creating awareness among HCWs regarding the current methods of cervical cancer screening is a necessary to reduce morbidity and mortality from cervical cancer in WLWH.